Review article: the efficacy of biomarkers in chronic fibroproliferative diseases – early diagnosis and prognosis, with liver fibrosis as an exemplar. Issue 3 (9th June 2014) - Karsdal, M. A.; Krarup, H.; Sand, J. M. B.; Christensen, P. B.; Gerstoft, J.; Leeming, D. J.; Weis, N.; Schaffalitzky de Muckadell, O. B.; Krag, A.
Summary Background Nearly 45% of all deaths are associated with chronic fibroproliferative diseases, of which the primary characteristic is altered remodelling of the extracellular matrix. A major difficulty in developing anti‐fibrotic therapies is the lack of accurate and established techniques to estimate dynamics of fibrosis, regression or progression, in response to therapy. Aim One of the most pressing needs in modern clinical chemistry for fibroproliferative disorders is the development of biomarkers for early diagnosis, prognosis, and early efficacy for the benefit of patients and to facilitate improved drug development. The aim of this article was to review the serological biomarkers that may assist in early diagnosis of patients, separate fast from slow‐ or nonprogressors, and possibly assist in drug development for fibroproliferative diseases, exemplified by liver fibrosis. The lack of success of biochemical markers and the possible reasons for this is discussed in the context of other fields with biomarker success. Method This is a personal opinion review article. Results Biochemical markers, originating from the fibrotic structure, may have increased specificity and sensitivity for disease. Assessment of the tissue turnover balance by measurement of tissue formation and tissue degradation separately by novel technologies may provide value. Conclusions Novel technologies focused on the protein fingerprint in addition to biomarker classification, may increase the quality of biomarker development and provide the much needed biomarkers to further the fibroproliferative field. This is in direct alignment with the Food and Drug Administration and European Medicinal Agencies initiatives of personal health care.